2010
DOI: 10.1063/1.3483612
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electron-electron scattering on transport characteristics in monolayer graphene

Abstract: The influence of electron-electron scattering on the distribution function and transport characteristics of intrinsic monolayer graphene is investigated via an ensemble Monte Carlo simulation. Due to the linear dispersion relation in the vicinity of the Dirac points, it is found that pair-wise collisions in graphene do not conserve the ensemble average velocity in contrast to conventional semiconductors with parabolic energy bands. Numerical results indicate that electron-electron scattering can lead to a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 23 publications
4
59
0
Order By: Relevance
“…In principle, this transport problem could be solved with the Monte-Carlo method, which is a powerful tool to treat various scattering mechanisms. 27,28 Instead, here we employ a hydrodynamic model that is computationally less demanding than the ensemble Monte Carlo method, especially when including self-consistently both self-heating effects and full inter-particle Coulomb interactions, which are important in graphene 29 The drift velocity vd and the electron temperature Te are determined from balancing momentum and energy gained by charge carriers from the electric field, with momentum and energy released through various scattering mechanisms. 30 We also introduce an insightful power dissipation and selfheating approach shown in Fig.…”
Section: A Transport Modelmentioning
confidence: 99%
“…In principle, this transport problem could be solved with the Monte-Carlo method, which is a powerful tool to treat various scattering mechanisms. 27,28 Instead, here we employ a hydrodynamic model that is computationally less demanding than the ensemble Monte Carlo method, especially when including self-consistently both self-heating effects and full inter-particle Coulomb interactions, which are important in graphene 29 The drift velocity vd and the electron temperature Te are determined from balancing momentum and energy gained by charge carriers from the electric field, with momentum and energy released through various scattering mechanisms. 30 We also introduce an insightful power dissipation and selfheating approach shown in Fig.…”
Section: A Transport Modelmentioning
confidence: 99%
“…Carrier scattering in supported graphene is attributed to a variety of sources including ripples in the graphene layer, point defects and their associated short-range potentials, electron-electron (hole-hole) interactions, charged impurities residing in the supporting substrate, and adsorbed atoms on the surface [5,6,7]. Earlier studies suggested that charged impurity scattering could explain the dominant behavior in experimental findings [5,8].…”
mentioning
confidence: 99%
“…However as the carrier density in the channel region increases the coulomb scattering becomes dominant scattering mechanism in SLG as reported in Ref. 16. In Ref.…”
Section: Introductionmentioning
confidence: 90%